The relationship between perfectionism, self-perception of orofacial appearance, and mental health in college students - Gao, Xinlin; Zhong, Jiawei; Li, Hanchao; Pei, Yapeng; Li, Xixin; Zhang, Siyu; Yue, Yuan; Xiong, Xin (Frontiers in Public Health, 2023)
Background In dental clinical practice, self-perception of orofacial appearance is highly correlated with treatment satisfaction. Therefore, it is important to explore factors correlated with self-perception of orofacial appearance. Perfectionism may be one such factor. This study investigated the role of perfectionism in self-perception of orofacial appearance. Methods Participants completed an online questionnaire that included demographic data, a measure of perfectionism, a measure of self-perception of orofacial appearance (including body image, smile appearance concern, and self-esteem), and a measure of anxiety and depression. Results High perfectionism scores significantly predicted greater age, body image, smile appearance concern, and mental health scores and lower self-esteem scores (p < 0.005). After adjusting for possible confounding variables, smile appearance concern largely disappeared. Mental health acted as a mediator in the relationships between perfectionism and three orofacial appearance characteristics. Conclusion High perfectionism predicted higher self-perception of body image, and lower mental health and self-esteem in college students. Mental health could mediate the relationships between perfectionism and self-perception of orofacial appearance.